Mapping the Integration of Computational Thinking in Mathematics Education: A Scopus-Based Bibliometric Analysis (2015–2025) - Eliska Juliangkary; I Nengah Suparta; I Made Ardana; Gusti Ayu Mahayukti (Program Studi Pendidikan Matematika, FSTT, Universitas Pendidikan Mandalika, 2025)
This study presents a comprehensive bibliometric analysis of research on Computational Thinking (CT) in mathematics education, based on Scopus-indexed publications from 2015 to 2025. CT—encompassing higher-order cognitive skills such as decomposition, pattern recognition, abstraction, and algorithmic thinking—has gained increasing relevance in 21st-century mathematics instruction. The study aims to map the development of research in this domain by analyzing seven key aspects: publication trends, author productivity, institutional productivity, journal productivity, international collaboration patterns, co-word relationships, and thematic evolution. A total of 165 English-language journal articles were analyzed using RStudio in conjunction with the Bibliometrix package. The results indicate a rapid annual publication growth rate of 23.11%, reflecting heightened global interest in the topic. Most publications resulted from collaborative research, with notable international partnerships, particularly involving Southeast Asian countries such as Indonesia. Frequently occurring keywords included